Implementasi NOSACQ-50, JSA dan Participatory Ergonomics untuk Mewujudkan Lingkungan Kerja yang Nyaman, Selamat, dan Humanum (Studi Kasus) - Paulus Sukapto; Harjoto Djojosubroto; Diartano Christian (Politeknik Kesehatan Tanjung Karang, 2019)
PT. PAI currently does not have an Occupational Safety and Health Management System (SMK3), which is a standard that companies must have with a workforce exceeding 100 people. The research objective is a case study to measure the occupational safety and health climate at the Department of Rubber, Stockfit, and Chemical Storage. The research conducted consists of measuring the potential hazards (determining the amount of work activity) using the Job Safety Analysis (JSA) Method; subsequently the highest risk level is measured based on the Risk Score Method; after which the work system was improved by using Participatory Ergonomics (PE). The results of the study indicate that JSA produced 10 work activities with the highest risk score, namely rubber cutting activity, primering activity, and buffing activity. Its improvement by using the Participatory Ergonomics (PE) Method results in rubber cutting activity by rearranging the laying of rubber in the warehouse to a vertical position; primering activity by replacing glue containers and brushes with special tools; and finally, the buffing activity by installing an exhaust fan.